O-L07 Role of liver resection for metastases from uveal melanoma: Experience from a supra-regional centre, current evidence, and future prospects. (16th December 2021) - Trivedi, Dharmadev; Aldulaimi, Natasha; Karydis, Ioannis; Wheater, Matthew; Modi, Sachin; Stedman, Brian; Karavias, Dimitrios; Primrose, John; Pearce, Neil; Takhar, Arjun
Abstract: Background: Management of liver metastases from uveal melanoma (LMUM) requires a 'multi-modal' approach including surgical resection. This study aimed to evaluate the role, safety, and oncological effectiveness of liver surgery for patients with LMUM in the context multidisciplinary management. A comprehensive treatment pathway developed upon current published evidence, prevalent national guidelines and novel treatment options is presented (Figure 2 ) Methods: Retrospective review of prospectively maintained database between February 2005 to August 2018 was performed using the institutional electronic patient record system from oncology and surgical department. Demographic data, MDT outcome letters, operative records, clinic letters, letters from referring hospitals, discharge summaries, radiology reports, and histology findings were reviewed. Focused literature review was conducted to identify all relevant publications. All advanced statistical analysis was performed using SPSS version 27.0 software (IBM Corp., Armonk, NY, USA). A p-value of < 0.05 was considered to be statistically significant. The work was approved by the institutional clinical governance department (Audit ID 6661). Results: 31 patients underwent diagnostic laparoscopy and 17 patients received 19 liver resections locally (Figure 1 ). 7 major (≥ 3 seg) and 12 minor liver resections (14 laparoscopic) were done without any mortality or major complications. 10/19 (52.6%) were R0 resections. Overall survival positively correlated with the time from UM to LMUM ( r s = 0.859, p <0.0001). R0 or R1 resection margin status did not significantly influence survival outcomes (OS 25 Vs 28, p = 0.404; RFS 13 Vs 6 months, p = 0.596), though R1 cohort had longer lead time (100 Vs 24 months, p = 0.0408). Conclusions: Liver resection for LMUM is safe, effective and complements multimodal management. Lead time from development of UM to LMUM remains a key factor affecting survival outcomes. As novel treatment modalities for regional and systemic disease control for metastatic uveal melanoma continue to develop, surgical intervention will also continue to evolve as part of the multi-disciplinary management. We emphasise the need for developing a collaborative database at a national and international level. We present an evidence-based, multi-disciplinary management pathway for LMUM patients (Figure 2 ).